Handheld XRF as a proxy for onsite evaluation of unconventional targets: an investigation of the Woodford shale, Anadarko basin, Oklahoma - Willey, Tyler Jayne (Kansas State University, 2015)
The Woodford shale is recognized as an abundant source rock across Oklahoma and much of the midcontinent (Lambert, 1990), and up to 8% of the world’s hydrocarbon reserves are estimated to have been sourced by the Woodford and its equivalents (Fritz et al, 1991). The Woodford shale is far more complex than other Devonian black shales found in North America due to the presence of alternating bands of chert-like amorphous silica and silica-rich shale. Analysis of chert and its possible role in gas generation and storage in shales has been largely overlooked. The goal of this study is to determine if chert size, amounts, or polycrystallinity can be indicators of thermal maturity within the Woodford shale. Handheld XRF analysis was conducted on the whole rock samples, and a mudrock specific sodium bisulfate fusion was used to separate the non-clay fraction. SEM was performed on the resulting separates to study and observe changes in chert fabric, grain-size, and amount. No correlations were observed to indicate that chert is an indicator of thermal maturity within the Woodford shale. Increase in chert growth and amount was also not detected within the size fractions as thermal maturity increases. Handheld XRF proved to be a good proxy for quick, onsite analysis of silica concentrations, as well as the amount of organic matter within drill core. This could be beneficial as hydraulic fracking produces best results in areas of higher silica content, and the wells with the highest organic matter have the highest potential for petroleum accumulations.
Keywords: Handheld XRF; Petroleum; Thermal Maturity; Anadarko Basin; Woodford Shale; illite; Geology (0372); Petroleum Geology (0583); Sedimentary Geology (0594)